(untitled) (Islamic Sciences Journal, 2023)
This research aims at clarifying the jurisprudential issues related to the interpretation of the goal of the wishes, for Al-Kurani in Surat Al-Mujadilait. It also clarify the relationship between Islamic jurisprudence and the main and secondary sources from which it is derived, such as the Holy Qur’an and the Sunnah of the Prophet, and to identify the difference in jurisprudence issues. That is leading to the result of the dispute, and thus it becomes clear to us. The issue in all its aspects is included into two sections, the first shows two demands: The first requirement: a clarification of the concept of jurisprudence, linguistically and idiomatically. The second is the amount of compensation for zihar